2001
DOI: 10.1063/1.1368376
|View full text |Cite
|
Sign up to set email alerts
|

Energy distributions of electrons emitted from GaAs(Cs, O)

Abstract: A method to map out the energy distribution N(E ʈ ,E Ќ ) of an electron beam as a function of the longitudinal (E ʈ ) and transverse (E Ќ ) energy has been developed and applied to study the photoemission process from GaAs͑Cs, O͒ at 90 K. The method proceeds by ''marking'' electrons with fixed longitudinal energy E ʈ b and a subsequent measurement of the associated differential transverse energy distribution N Ќ (E ʈ b ,E Ќ ), applying an adiabatic magnetic compression technique. The complete energy distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…One attempt of operating photocathodes at cryogenic temperature was performed using GaAs [15] cooled to 90 K. The electron beam properties were studied using a dedicated electron energy analyzer [16] but the results showed that at 90 K MTEs of about 75 meV were achieved (corresponding to about 900 K) because of the long tails on the electron energy distribution. Authors claimed that if a longitudinal energy filter is used to cut off electrons with smaller longitudinal energies, MTEs of 5-7 meV might be obtained from the cryocooled GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…One attempt of operating photocathodes at cryogenic temperature was performed using GaAs [15] cooled to 90 K. The electron beam properties were studied using a dedicated electron energy analyzer [16] but the results showed that at 90 K MTEs of about 75 meV were achieved (corresponding to about 900 K) because of the long tails on the electron energy distribution. Authors claimed that if a longitudinal energy filter is used to cut off electrons with smaller longitudinal energies, MTEs of 5-7 meV might be obtained from the cryocooled GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the overall energy distribution from a photocathode is about the same or even worse as compared to thermocathodes. However, it was found that electrons emitted above a suitable longitudinal energy (≥E c ) have transverse and longitudinal spreads of about the bulk temperature [5,11]. For these electrons energy spreads of about 5-7 meV and 25 meV were measured at 90 K and 300 K, respectively [5,10].…”
Section: Photoelectron Emission From Gaas(cso)mentioning
confidence: 99%
“…Electrons, photoexcited from the valence band to the conduction band, are rapidly thermalized at the bottom of the conduction band and reach the surface with energy spreads defined by the temperature of the bulk, which is in our case about 80 K. Due to the NEA condition, a large fraction of these electrons can escape into the vacuum. However, during the escape process electrons undergo strong energy and momentum relaxation [5]. As a result they occupy the complete available phase space, enlarging the transverse and longitudinal energy spreads to about the value of the NEA (typically about 150-250 meV).…”
Section: Photoelectron Emission From Gaas(cso)mentioning
confidence: 99%
See 2 more Smart Citations